Towards the modeling of the ditching of a ground-effect wing ship within the framework of the SPH method. (January 2019) - Cheng, H.; Ming, F.R.; Sun, P.N.; Wang, P.P.; Zhang, A.M.
Abstract: Ditching often takes place for a ground-effect wing (WIG) ship. During the ditching, the extreme load developed by water impacts may cause damages to structures, posing a great threat to the safety of crew and passengers. In the paper, a weakly compressible smoothed particle hydrodynamics (SPH) model combined with enhanced numerical techniques has been adopted to tackle the ditching problems. In order to handle the motion of a rigid body in the three-dimensional ditching problems, the six degrees-of-freedom (6-DOF) equations of motion are incorporated into the SPH scheme. The accuracy of the SPH model is validated through two benchmarks, respectively, the two-dimensional wedge water entry and the three-dimensional stone-skipping. The former is aimed to validate the prediction of pressures during the free surface impact while the latter is a good case for testing the coupling motions of the rigid body. Furthermore, the ditching of the real scale WIG ship under different conditions is simulated with the established SPH model, through which some useful conclusions are drawn.